The general public’s attitude towards accepting payment for kidney donation - Gonen, Limor Dina; Bokek-Cohen, Ya’arit; Tarabeih, Mahdi (Frontiers in Medicine, 2023)
Introduction: Kidney transplantation has become the most cost-effective treatment for patients with end-stage kidney disease (ESKD) and offers them the highest quality of life. Yet, kidney donation is often inaccessible due to cultural and traditional beliefs about organ donation. The goal of our study is to assess the value of kidney donation using the Willingness to Accept (WTA) technique. We also aim to understand the factors influencing an individual's willingness to donate an organ. Method: A self-administered survey was completed by 985 participants from the general public. The quantitative method and survey design that were chosen used descriptive, correlational, nonparametric, and multivariate statistical tests. Results: Most of the respondents, 895 (90.9%) are not willing to donate a kidney while alive. Four hundred and five (41.1%) of the respondents are not willing to donate a kidney after their death, while the rest are willing to donate their kidney after their death without financial compensation. The same attitude applies to the donation of a kidney from their relatives. Significant predictors from the results of the logistic regression model in predicting the lowest (minimal) amount that will encourage donation of one kidney after death were: Marital status; Nationality; Adi card holder; Knowing people who need a kidney donation; Confidence in the medical staff; and Consideration of the family's opinions regarding organ donation. Discussion: Using cost benefit analysis (CBA), with the aim of evaluating the willingness of individuals to accept payment for innovative medical procedures, such as kidney donation, allows an assessment of the perceived value of the medical procedure and enables policymakers to decide whether to allocate funds or offer subsidies for kidney donation, given the limited healthcare resources available. During our research, we found that most participants did not support the commercialization of organs. Our recommendation for policymakers and health professionals is to continue providing adequate funding for kidney donations and to implement educational programs aimed at improving attitudes towards organ donation.